Bacterial Vaginosis: A Review of Pathophysiology, Epidemiology, Complications, Diagnosis, and Treatment - Nasir, Rida; Guilherme, Stephen; Puca, Daisy; Menoudakos, Demetra; Wang, Jeffry; Hall, Rochelle; Cheta, Melissa; Iyeke, Lisa; Richman, Mark (Europasian Journal of Medical Sciences, 2023)
Bacterial vaginosis (BV) is the most-common cause of abnormal vaginal discharge among women of reproductive age, though many are asymptomatic. It is caused by the replacement of normal vaginal Lactobacillus with Gram-negative and anaerobic organisms. BV has assumed increasing public health importance through associations with numerous adverse outcomes in both gravid and non-gravid women. Risk factors for BV include smoking, non-White race, prior BV, current other sexually transmitted diseases (STDs), inserting items in the vagina (e.g., sex, douching), and menses. Symptomatic BV has been associated with pelvic inflammatory disease (PID), miscarriage, premature rupture of membranes, chorioamnionitis, premature labor and delivery, postpartum endometritis, and post-hysterectomy vaginal cuff cellulitis. Anaerobic Gram-negative rods common to BV have also been independently associated with endometritis or PID, even in the absence of clinical BV. BV has also been independently associated with an increased risk of acquiring STDs, including acquiring and transmitting HIV. BV is not an STD, though recent sexual intercourse and multiple sex partners are risk factors. BV causes a malodorous, white or gray vaginal discharge and is diagnosed through Amsel’s criteria. Treatment with metronidazole or clindamycin is important for symptom relief and to prevent adverse obstetric consequences, particularly among high-risk women who have had a previous preterm delivery or have a pre-pregnancy weight <50 kg.